2021
DOI: 10.1177/1535370220988246
|View full text |Cite
|
Sign up to set email alerts
|

High ROBO3 expression predicts poor survival in non-M3 acute myeloid leukemia

Abstract: Roundabout guidance receptor proteins are crucial components of the SLIT/ROBO signaling pathway. This pathway is important for the nervous system and in embryonic development. Recently, increasing evidence has shown that roundabout guidance receptor proteins and the SLIT/ROBO signaling pathway also participate in tumorigenesis. Here, by analyzing transcriptome data from the TCGA and GEO databases, we found that ROBO3 is highly expressed in non-M3 acute myeloid leukemia. High ROBO3 expression was associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…SLIT/ROBO, a ligand/ receptor family first identified in neuronal guidance, 52 appears to be involved in AML biology, 53 and increased pathway activity may constitute a risk factor for poor survival. 54 However, it has not yet been linked to daunorubicin treatment response in AML patients. Neddylation, a ubiquitin-like posttranslational protein modification, is required for cancer cell growth and survival.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SLIT/ROBO, a ligand/ receptor family first identified in neuronal guidance, 52 appears to be involved in AML biology, 53 and increased pathway activity may constitute a risk factor for poor survival. 54 However, it has not yet been linked to daunorubicin treatment response in AML patients. Neddylation, a ubiquitin-like posttranslational protein modification, is required for cancer cell growth and survival.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Our data from this proof-of-concept ex vivo study of a single AML patient uncovered previously identified pathways modulated by daunorubicin and implicates the neddylation and SLIT/ROBO pathways as possible new targets for cotreatment with daunorubicine. SLIT/ROBO, a ligand/receptor family first identified in neuronal guidance, appears to be involved in AML biology, and increased pathway activity may constitute a risk factor for poor survival . However, it has not yet been linked to daunorubicin treatment response in AML patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study had demonstrated that ROBO3 was overexpressed in AML and associated with poor prognosis (Cai et al, 2021, Gołos et al, 2019, but it did not distinguish the therapeutic outcome of chemotherapy and allo-HSCT based on ROBO3 expression. As we all know, the prognostic value of a biomarker is treatment-dependent in AML.…”
Section: Introductionmentioning
confidence: 95%